POTENSI DAUN KEMANGI (Ocimum sanctum L.) TERHADAP BAKTERI Bacillus cereus - tri Sudarwati; Tri Hajar (Jurnal Komunitas Farmasi Nasional, 2022)
Ocimum sanctum L. is the main essential oil plant that is commercially cultivated in many countries. The purpose of the study was to determine the ability of basil leaf extract (Ocimum sanctum L.) in inhibiting the growth of Bacillus cereus bacteria. Bacillus cereus will grow when the substrate contains carbohydrates. Food poisoning occurs in general because it contains a high amount of Bacillus cereus bacteria. The research design used in this study is an analytical type based on an analytical review littarature. Researchers use the Google Scholar database. The data used in this study comes from the results of research that has been published in national and international online journals. Based on the results of the resume of articles, it is known that basil leaf extract (Ocimum sanctum L.) can inhibit the growth of bacillus cereus bacteria. Inhibition zones formed because basil leaves contain flavonoids, alkaloids, saponins and tannins which are antibacterial. The solvent used in the manufacture of extraction is ethanol because it is universal. diffusion inhibition power test method, Diameter of the formed inhibitory zone is classified in several categories. Basil leaf extract has an antibacterial influence on a concentration of 100% with a large inhibitory zone of 11±1.73 mm belonging to the category of strong.